2005
DOI: 10.1051/0004-6361:20041135
|View full text |Cite
|
Sign up to set email alerts
|

Close binary companions of the HAeBe stars LkHα198, Elias 1, HK Ori and V380 Ori

Abstract: Abstract. We present diffraction-limited bispectrum speckle interferometry observations of four well-known Herbig Ae/Be (HAeBe) stars, LkHα 198, Elias 1, HK Ori and V380 Ori. For two of these, LkHα 198 and Elias 1, we present the first unambiguous detection of close companions. The plane of the orbit of the new LkHα 198 companion appears to be significantly inclined to the plane of the circumprimary disk, as inferred from the orientation of the outflow. We show that the Elias 1 companion may be a convective st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…There are however remarkable exceptions to this general rule. For instance, both the outflow and the binary orbit of the LkHα 198 system lie close to the plane of the sky, indicating that the circumstellar disk is nearly orthogonal to the binary orbit (Smith et al 2005). A strong argument can also be made in the PDS 144 system, where one of the two components has its disk viewed almost exactly edge-on while the other lies at a lower inclination, indicating that the two disks are misaligned by about 25…”
Section: Circumstellar Disks In Wide Binariesmentioning
confidence: 97%
“…There are however remarkable exceptions to this general rule. For instance, both the outflow and the binary orbit of the LkHα 198 system lie close to the plane of the sky, indicating that the circumstellar disk is nearly orthogonal to the binary orbit (Smith et al 2005). A strong argument can also be made in the PDS 144 system, where one of the two components has its disk viewed almost exactly edge-on while the other lies at a lower inclination, indicating that the two disks are misaligned by about 25…”
Section: Circumstellar Disks In Wide Binariesmentioning
confidence: 97%
“…Next to the primary of spectral type B9...A6 the system includes a T Tauri type companion at a separation of ∼4 (Leinert et al 1997). Smith et al (2005) discovered a further faint companion with estimated mass of 1.5−2 M at only 50 mas from the HAeBe star.…”
Section: A2 V892 Taumentioning
confidence: 99%
“…A few studies have focused on a search for close visual binaries (e.g. Li et al 1994;Pirzkal et al 1997;Leinert et al 1997;Smith et al 2005). Monte Carlo simulations by Pirzkal et al (1997) have suggested that almost all HAeBe stars have companions within a completeness limit of K < 10.5 mag for separations of 0.4...8 .…”
Section: Introductionmentioning
confidence: 99%
“…Rebull et al (2010) report it as a flat-spectrum source in the near-to-far-IR, having L IR /L total = 0.089. V892 Tau is a double-star system (Smith et al 2005) with a circumbinary disk (Monnier et al 2008).…”
Section: V892 Taumentioning
confidence: 99%